Modified anatomical reconstruction for symptomatic chronic acromioclavicular joint disruption: surgical technique and case reports - Mohd Sabari, Qiuzi Iqbal; Goh, Kian Liang; Awang, Shukrimi; Mohd Yusof, Nazri; Che Ahmad, Aminudin (2011)
Acromioclavicular joint (AC) separations are common injuries seen in orthopedics and sports trauma practices; and accounting for 9% of all injuries to the shoulder girdle. Management of AC joint problems is dictated by the severity and chronicity of the injury as well as the patient's needs and expectations. This technique is designed io stabilize the acromioclavicular joint by recreating the anatomy of the coracoclavicular and acromioclavicular ligaments simultaneously via a single approach in contrast to the classic Weaver-Dunn procedures. We are describing a modified surgical technique, namely an anatomical stabilization using a Tight-Rope® (Arthrex, Naples, FL, USA) for coracoclavicular ligament and multiple suture loops for acromioclavicular ligaments in chronic cases.